(untitled) (Economics and region, 2018)
System of region’s social and economic security is considered. Initial parameters of region’s social and economic security based on system approach, its components and features are defined. The main factors influencing the region’s social and economic security include macroeconomic resources, social, institutional, political and informational support ones. The necessity of creation a system of regions’ social and economic security indicators according to its separate components is substantiated. A range of unsettled problems which prevent achieving social and economic security at the regional level is specified. It is noted that natural combination of the state, regional and local interests contributes to maximally full usage of each region and place internal potential. Priorities of regional social and economic policy in terms of budget decentralization are defined. The aim of regions of Ukraine social and economic security which consists in ensuring social balance, economic stability and development is substantiated, under which regions’ social and economic provision objectives are stated. It is proved that region’s economy development is one of the main preconditions for providing regions of Ukraine social and economic security. The necessity of more effective usage of regions internal potential in terms of limited budget and other resources is substantiated. Conditions for regions of Ukraine social and economic security provision under widening regions economic abilities are defined, including competitiveness increase, support and strengthening of scientific and technical, human resources potential, inflation rate shortening, worsening ecological situation, increase in the people of Ukraine standard of living.